Misconception Analysis of Human Circulatory System Material in Biology Textbook Class XI High School Based on Curriculum 2013 - Risa Umami; Evi Elidayani; Alwan Mahsul (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2022)
This study aims to determine the existence of misconceptions, types of misconceptions, and the percentage of misconceptions about the human circulation system material in the 2013 curriculum-based high school biology textbooks. This research is a descriptive qualitative study that aims to describe misconceptions about the human circulation system material in biology textbooks in class XI SMA based on the 2013 curriculum with the object being analyzed in the form of three books used in schools. The unit of analysis in this study is in the form of text concepts that contain material on the human circulation system. The instrument used is a misconception analysis sheet. The results of the study showed that there were misconceptions in the three biology textbooks, namely in books A, B, and C with the category of misconceptions-misidentifications. There are 3 misconceptions in books B and C while in book A there are 2 concepts that experience misconceptions. The percentage of misconceptions in book A is 0.9%, book B is 1.9% and book C is 2.4%.